PENGARUH PELAYANAN, PENGAWASAN DAN KONSULTASI YANG DILAKSANAKAN OLEH ACCOUNT REPRESENTATIVE SERTA PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN YANG TERDAFTAR DI KPP MADYA PEKANBARU - Retno Sukmawati; Zirman -; Al Azhar Ali (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The main purpose of this research is examining and knowing the efffects of servicing, controlling and consultating of Account Representative and also tax audit on corporate taxpayers compliance. The population in this study were the whole corporate taxpayers registered with the Kantor Pelayanan Pajak (KPP) Madya Pekanbaru, with the population total 1.345 corporates per June 2014, and the sample total 100 corporates. The sample are taken by using purposive sampling method. Type and data source in this study is survey and primer data such as questionnaire. This research use multiple linear regression anaysis to examine the factors that are predicted to affect independence variabels of dependence variabel. The result of this research show that servicing and controlling of Account Representative and also tax audit effected on corporates taxpayers compliance. Then, consultating of Account Representative does not have significant effect on corporates taxpayer compliance.Keywords: Servicing, Controlling, Consultating, Tax Audit, and Tax Compliance